Объяснение:
H2SO4 + 2NaOH = Na2SO4 + 2H2O
2H(+) + SO4(2-) + 2Na(+) + 2OH(-) = 2Na(+) + SO4(2-) + 2H2O
2H(+) + 2OH(-) = 2H2O
FeCl2 + 2NaOH = Fe(OH)2↓ + 2NaCl
Fe(2+) + 2Cl(-)+ 2Na(+) + 2OH(-) = Fe(OH)2↓ + 2Na(+) + 2Cl(-)
Fe(2+) + 2OH(-) = Fe(OH)2↓
CaCO3 + 2HCl = CaCl2 + CO2↑ + H2O
CaCO3 + 2H(+) + 2Cl(-) = Ca(2+) + 2Cl(-) + CO2↑ + H2O
CaCO3 + 2H(+) = Ca(2+) + CO2↑ + H2O
Na2SO3 + 2HCl = 2NaCl + SO2↑ + H2O
2Na(+) + SO3(2-) + 2H(+) + 2Cl(-) = 2Na(+) + 2Cl(-) + SO2↑ + H2O
SO3(2-) + 2H(+) = SO2↑ + H2O
Ca(OH)2 + Na2SiO3 = CaSiO3↓ + 2NaOH
Ca(OH)2 + 2Na(+) + SiO3(2-) = CaSiO3 + 2Na(+) + 2OH(-)
Ca(OH)2+ SiO3(2-) = CaSiO3 + 2OH(-)
2H(+) + SO4(-2)+ 2Na(+) + 2OH(-) -> 2Na(+) + SO4(-2)+ 2H2O
2H(+) + 2OH(-) -> 2H2O
2) 2HCl + Cu(OH)2 -> CuCl2 + 2H2O
2H(+) + 2Cl(-) + Cu(OH)2 -> Cu(+2) + 2Cl(-)+ 2H2O
2H(+) + Cu(OH)2 -> Cu(+2) + 2H2O
3) 2NaOH + MgCl2 -> Mg(OH)2 + 2NaCl
2Na(+) + 2OH(-) + Mg(+2) + 2Cl(-)-> Mg(OH)2 + 2Na(+) + 2Cl(-)
Mg(+2) + 2OH(-)-> Mg(OH)2
4) 2NaOH + SO3 -> Na2SO4 + H2O
2Na(+) + 2OH(-)+ SO3 -> 2Na(+) + SO4(-2) + H2O
2OH(-)+ SO3 -> SO4(-2) + H2O